Relación entre el autoconcepto de las competencias, las metas académicas y el rendimiento en alumnos universitarios de la ciudad de Lima - Escurra Mayaute, Luis Miguel (2005)
OBJECTIVE: To study the relationship between abilities selfconcept, academic goals and performance among college students of the city of Lima, Peru. DISEGN: Multivariate correlational study on college students from Lima and Callao. INSTRUMENTS AND METHODS: Stratifical sampling was used considering the quantity of students at college, academic school, and level of studies. The sample were 1018 college students. It was used the selfconcept scale of abilities and the academic goals scale. The statistical analysis was done in three stages: Psychometric in order to evaluate validity and reliability; descriptive and bivariate and multivariate approach (multiple regression analysis) hypothesis testing. RESULTS: The students mean age was 21.1 +/- 2.41 years old and 66.6% were female and 33.4% were male. Students from public and private colleges were 53% and 47% respectively. CONCLUSIONS: Findings show that the selfconcept scale of abilities and the academic goals questionnaire have validity and reliability. The scores on both scales showed a normal distribution. there are significative correlations between the scores of the selfconcept abilities and academic goals scales; selfconcept abilities and academic performance; academic goals and academic performance, and selfconcept abilities, academic goals and academic performance. The comparative analysis shows that there are significative differences considering sex and level of studies. The selfconcept of abilities and the academic goals affect positively the academic performance.